Between a rock and a hard place: Vulnerability and precarity in rural Nepal. (November 2016) - Rigg, Jonathan; Oven, Katie J.; Basyal, Gopi Krishna; Lamichhane, Richa
Highlights: A distinction is drawn between inherited vulnerability and produced precarity. Development may reduce vulnerability but increase precarity, creating 'new' poverty. Vulnerability is therefore re-worked as precarity. Development-as-modernisation in Nepal has exposed households in new ways. Abstract: Drawing on a local study on Nepal's Terai, this paper explores the nature of livelihood exposure to shocks and stresses among rural households in two Village Development Committees in Sunsari District. The primary data are derived from a 117 household survey supplemented by 19 purposefully sampled follow-up interviews. The paper opens with a discussion of the changing nature of exposure in the global South, distinguishing between inherited vulnerability and produced precarity. We then provide background to the research site and the research methods. In the core empirical part of the paper we unravel and distinguish between the livelihood threats and opportunities faced by households in the area and use these to reflect on the nature of 'exposure', its historical origins and contemporary (re)production. The final part of the paper uses the Nepal case to build a more general argument, proposing that if we are to understand the puzzle of continued livelihood exposure and uncertainty in the context of aggregate economic expansion we need to identify and interrogate the processes that may, at the same time, produce wealth and reduce vulnerability, while also generating precarity.